Answer:
-2, -13
0, -3
2, 7
4, 17
Step-by-step explanation:
To fill out the table, substitute the table x-values into the equation and the y-values will fill the table.
y = 5x - 3
y = 5(-2) - 3
y = -10 - 3
y = -13
This means the table value corresponding to -2 should be -13.
y = 5x - 3
y = 5(0) - 3
y = 0 - 3
y = -3
This means the table value corresponding to 0 should be -3.
y = 5x - 3
y = 5(2) - 3
y = 10 - 3
y = 7
This means the table value corresponding to 2 should be 7.
y = 5x - 3
y = 5(4) - 3
y = 20 - 3
y = 17
This means the table value corresponding to 4 should be 17.
Answer:
3 x (14-3) = 33
Step-by-step explanation:
Answer:
A.(-2, 0)
C. (-1.4)
Step-by-step explanation:
we know that
If a point lie on the line, then the point must satisfy the equation of the line (makes the equation true)
we have
![8x-2y+7=-9](https://tex.z-dn.net/?f=8x-2y%2B7%3D-9)
subtract 7 both sides
![8x-2y=-9-7](https://tex.z-dn.net/?f=8x-2y%3D-9-7)
![8x-2y=-16](https://tex.z-dn.net/?f=8x-2y%3D-16)
divide by 2 both sides
![4x-y=-8](https://tex.z-dn.net/?f=4x-y%3D-8)
Substitute the value of x and the value of y of each point in the linear equation and analyze the result
<u><em>Verify each point</em></u>
case A) we have
(-2, 0)
For x=-2, y=0
substitute
![4(-2)-(0)=-8](https://tex.z-dn.net/?f=4%28-2%29-%280%29%3D-8)
---> is true
so
the point lie on the line
case B) we have
(1, 3)
For x=1, y=3
substitute
![4(1)-(3)=-8](https://tex.z-dn.net/?f=4%281%29-%283%29%3D-8)
---> is not true
so
the point not lie on the line
case C) we have
(-1, 4)
For x=-1, y=4
substitute
![4(-1)-(4)=-8](https://tex.z-dn.net/?f=4%28-1%29-%284%29%3D-8)
---> is true
so
the point lie on the line
case D) we have
(1, -4)
For x=1, y=-4
substitute
![4(1)-(-4)=-8](https://tex.z-dn.net/?f=4%281%29-%28-4%29%3D-8)
---> is not true
so
the point not lie on the line
case E) we have
(0, -1)
For x=0, y=-1
substitute
![4(0)-(-1)=-8](https://tex.z-dn.net/?f=4%280%29-%28-1%29%3D-8)
---> is not true
so
the point not lie on the line
Answer:
The value of your expression is 7/12x +1.
Step-by-step explanation:
1/4x + 3 - 1/3x + -2 First, positive and negative is negative
= 1/4x + 3 - 1/3x -2 Combine like terms, 1/4x and 1/3x
= 7/12x + 3 - 2 Combine like terms, +3 and -2
= 7/12x +1
Like terms are when a number have similar exponents bases, variables or just plain numbers.
3x, 4x, 5x
1.02x^2, 1.02x^3
<h3><u><em>
Please rate this and please give brainliest. Thanks!!!
</em></u></h3><h3><u><em>
Appreciate it! : )
</em></u></h3><h3><u><em>
And always,
</em></u></h3><h3><u><em>
SIMPLIFY BANANAS : )</em></u></h3><h3><u><em>
</em></u></h3>
<u><em></em></u>
A. f(x)= 100*1.04^t
Exponential functions follow the form of y=ab^x, where a is the principal amount, b is the rate of growth or decay (1+0.04), and x is the time.
b. f(8)= 100*1.04^8
100*1.368569...
136.856
Final answer: $136.86